Intervensi holistik sebagai terapi nonfarmakologis pada demensia: Tinjauan pustaka - Halimsetiono, Elita (JURNAL KESEHATAN PRIMER, 2022)
Introduction: Dementia can interfere with social and professional activities, reflected in the activities of daily life and the behavior of sufferers. Pharmacological and nonpharmacological interventions have been recommended to reduce the frequency and severity of symptoms, but nonpharmacological interventions are considered the preferred treatment alternative. This article aims to provide an overview of holistic interventions as nonpharmacological therapy for dementia. Methods: This article is a literature review using the keywords dementia, cognitive stimulation, reality orientation, reminiscence, and validation therapy through databases at Google Scholar, PubMed, NCBI, Wiley, APA, and the Cochrane Library. Inclusion criteria were in the form of national and international scientific articles and research reports for the last ten years which can be downloaded in full-text papers, and discuss holistic interventions as nonpharmacological therapy in dementia totaling 23 articles and two research reports. Results: Holistic interventions consisting of cognitive stimulation therapy, reality orientation therapy, reminiscence therapy, and validation therapy can improve cognition, quality of life, and psychological well-being; reduce symptoms of depression and behavioral disorders; provide opportunities for social interaction; is non-invasive, safe, cost-effective, and easy to implement; and can be performed in a variety of environments. Conclusion: Holistic intervention is a nonpharmacological therapy that is very beneficial for people with dementia, so it can be considered an alternative treatment option for dementia.